Run-time reconfiguration for efficient tracking of implanted magnets with a myokinetic control interface applied to robotic hands - Mendez, Sergio Andres Pertuz (2021)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2021.